Negative electrode composition, negative electrode for lithium secondary battery comprising same, and lithium secondary battery comprising same
By using silicon-based active materials, pores and linear conductive materials in the negative electrode of lithium secondary batteries, the problem of conduction path disconnection caused by volume expansion during charging is solved, and the maximum diffusion of lithium ions and optimization of battery performance is achieved.
Patent Information
- Application Number
- CN202380054478.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-16
- Filing Date
- 2023-12-15
- Publication Date
- 2025-02-25
AI Technical Summary
When using silicon-based compounds as the negative electrode active material, the volume expands rapidly during charging, resulting in disconnection of the conductive path and reducing battery characteristics. The existing measures are limited and difficult to implement in commercialization.
A negative electrode composition containing silicon-based active material, pore-assisting material and linear conductive material is adopted to ensure that the material maintains the electrode porosity through the holes, and to ensure the non-conductive characteristics of the material through the linear conductive material to reduce the electrode resistance.
While maintaining electrode porosity, it maximizes the diffusion of lithium ions, extends the battery life, improves fast charging performance, and optimizes battery capacity characteristics and energy density.
Smart Images

Figure CN119522488A_ABST
Abstract
Description
Technical Field
[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0177386 filed in the Korean Intellectual Property Office on December 16, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to a negative electrode composition, a negative electrode for a lithium secondary battery including the negative electrode, and a lithium secondary battery including the negative electrode. Background Art
[0003] Due to the rapid increase in the use of fossil fuels, the demand for using alternative or clean energy is increasing, and as part of this trend, the most active research field is the field of power generation and storage using electrochemical reactions.
[0004] Currently, representative examples of electrochemical devices using such electrochemical energy include secondary batteries, and their use fields are increasingly expanding.
[0005] With the development of technology of mobile devices and the increase of demand for them, the demand for secondary batteries as energy sources has increased rapidly. Among such secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as electrodes for such high-capacity lithium secondary batteries, methods for preparing high-density electrodes with higher energy density per unit volume have been actively studied.
[0006] Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode contains a negative electrode active material for inserting and extracting lithium ions from the positive electrode, and as the negative electrode active material, silicon-based particles having a high discharge capacity can be used.
[0007] In particular, in recent years, in response to the demand for high-density energy batteries, a method of increasing capacity by using silicon-based compounds such as Si / C or SiOx, which have a capacity 10 times or more as high as that of graphite-based materials, as negative electrode active materials has been actively studied. However, silicon-based compounds as high-capacity materials have a large capacity compared to the currently used graphite, but there is a problem in that the volume expands rapidly during the charging process, the conductive path is disconnected, and thus the battery characteristics are reduced.
[0008] Therefore, in order to solve the problems when silicon-based compounds are used as negative electrode active materials, measures for adjusting the driving potential, as well as measures for suppressing the volume expansion itself, such as a method of further coating the active material layer with a thin film and a method of adjusting the particle size of the silicon-based compound, various measures to prevent the conductive path from being disconnected, etc. have been discussed. However, since the performance of the battery may deteriorate, there are limitations in the application of these measures, so that there are still limitations in the commercialization of the preparation of batteries with negative electrodes having a high content of silicon-based compounds.
[0009] In addition, in the case of an electrode using a graphite system or a graphite-silicon composite as an active material, the electrode is manufactured by adding a point-like conductive material, but the existing point-like conductive material reacts with lithium, increases the diffusion resistance of Li ions by blocking the pores in the electrode structure, and this resistance causes the degree of degradation of the electrode to be different between the upper and lower ends of the electrode during the lithium insertion / deinsertion reaction.
[0010] Therefore, in the process of manufacturing a silicon-based negative electrode for maximizing capacity characteristics, it is necessary to develop an electrode that can maximize the diffusion of Li ions while maintaining the porosity of the electrode at the same level.
[0011] <Related technical literature>
[0012] (Patent Document 1) Japanese Patent Application Publication No. 2009-080971 Summary of the invention
[0013] [Technical issues]
[0014] Although various types of negative electrode conductive materials have been used to maintain the conductive path, the above problems have not been solved. Therefore, when the dot-shaped conductive material as the existing conductive material is removed, a pore-ensuring material is included in the negative electrode composition to ensure pores in the electrode, and a linear conductive material is added thereto as a conductive material to compensate for the pore-ensuring material as a non-conductor, it is found that the above problems can be solved.
[0015] Therefore, the present application relates to a negative electrode composition capable of solving the above problems, a negative electrode for a lithium secondary battery including the negative electrode, and a lithium secondary battery including the negative electrode.
[0016] [Technical solution]
[0017] An exemplary embodiment of the present specification provides a negative electrode composition, the negative electrode composition comprising: a silicon-based active material; a pore ensuring material; a linear conductive material; and a negative electrode binder, wherein the silicon-based active material comprises one or more selected from the group consisting of SiOx (x=0) and SiOx (0<x<2), and based on 100 parts by weight of the silicon-based active material, the content of SiOx (x=0) is 90 parts by weight or more, based on 100 parts by weight of the negative electrode composition, the content of the pore ensuring material is 0.1 parts by weight or more and 20 parts by weight or less, and the weight ratio of the linear conductive material: the pore ensuring material is 1:10 to 1:120.
[0018] Another exemplary embodiment is directed to providing a negative electrode for a lithium secondary battery, the negative electrode comprising: a negative electrode collector layer; and a negative electrode active material layer formed on one surface or both surfaces of the negative electrode collector layer, the negative electrode active material layer comprising the negative electrode composition according to the present application.
[0019] Finally, the present specification is directed to providing a lithium secondary battery, which includes: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
[0020] [Beneficial Effects]
[0021] The negative electrode composition according to the present application is characterized in that a pore ensuring material capable of maximizing the diffusion of lithium ions while maintaining the porosity of the electrode is added. Therefore, since the dot-shaped conductive material as the existing conductive material is removed and the pore ensuring material is used, the pore ensuring material is located between the particles in the electrode, thereby having the advantage of ensuring pores capable of diffusing lithium ions.
[0022] In addition, the pore securing material is a non-conductor and is characterized in that pores are secured by using a certain content, and a linear conductive material is additionally contained to compensate for the pore securing material and reduce electrode resistance. Therefore, the pore securing material has the characteristics of being able to maintain pores even during insertion and extraction of lithium in a pure Si electrode, and also securing conductivity and reducing electrode resistance.
[0023] That is, the main feature of the negative electrode composition according to the present invention is that, in the negative electrode using a silicon-based active material in order to maximize the capacity, a certain content of pore ensuring material is used to simplify the pore structure that is a problem of pure Si, and the conductive network problem caused by this is solved by including a specific content of linear conductive material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1is a diagram showing a stack structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application.
[0025] Figure 2 is a diagram illustrating a stack structure of a lithium secondary battery according to an exemplary embodiment of the present application.
[0026] Figure 3 is a diagram showing a 4-point probe setup for calculating electrode conductivity.
[0027] <Description of symbols>
[0028] 10: Negative electrode collector layer
[0029] 20: Negative electrode active material layer
[0030] 30: Diaphragm
[0031] 40: Positive electrode active material layer
[0032] 50: Positive electrode collector layer
[0033] 60: External probe
[0034] 70: Internal probe
[0035] 100: Negative electrode for lithium secondary battery
[0036] 200: Positive electrode for lithium secondary battery DETAILED DESCRIPTION
[0037] Before describing the present invention, some terms are first defined.
[0038] In the present specification, when a part “comprises” one constituent element, unless otherwise specifically described, this does not mean that other constituent elements are excluded but means that other constituent elements may be further included.
[0039] In this specification, “p to q” means a range of “p or more and q or less”.
[0040] In this specification, "specific surface area" is measured by the BET method, and specifically calculated from the amount of nitrogen adsorbed at liquid nitrogen temperature (77K) using BELSORP-mini II manufactured by BEL Japan Co., Ltd. That is, in this application, the BET specific surface area may mean the specific surface area measured by the measurement method.
[0041] In this specification, "Dn" means particle size distribution, and means the particle size at n% point according to the cumulative distribution of the number of particles of particle size. That is, D50 is the particle size (median particle size) at 50% point according to the cumulative distribution of the number of particles of particle size, D90 is the particle size at 90% point according to the cumulative distribution of the number of particles of particle size, and D10 is the particle size at 10% point according to the cumulative distribution of the number of particles of particle size. On the other hand, the median particle size can be measured using a laser diffraction method. Specifically, after the powder to be measured is dispersed in a dispersion medium, the obtained dispersion is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500) to measure the difference in the diffraction pattern of the particle size when the particle passes through the laser beam, thereby calculating the particle size distribution.
[0042] In an exemplary embodiment of the present application, the particle size or particle diameter may mean an average diameter or a representative diameter of each particle forming the particle.
[0043] In the present specification, the fact that a polymer contains a monomer as a monomer unit means that the monomer participates in a polymerization reaction and is therefore contained in the polymer as a repeating unit. In the present specification, when a polymer contains a monomer, it is interpreted as the same as when the polymer contains a monomer as a monomer unit.
[0044] In this specification, unless otherwise specified as a "homopolymer", "polymer" should be understood to be used in a broad sense including copolymers.
[0045] In this specification, weight average molecular weight (Mw) and number average molecular weight (Mn) are polystyrene conversion molecular weights measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) with various polymerization degrees for measuring molecular weight as standard materials. In this specification, unless otherwise described, molecular weight means weight average molecular weight.
[0046] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings so that a person skilled in the art to which the present invention pertains can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.
[0047] An exemplary embodiment of the present specification provides a negative electrode composition, the negative electrode composition comprising: a silicon-based active material; a pore ensuring material; a linear conductive material; and a negative electrode binder, wherein the silicon-based active material comprises one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) is 90 parts by weight or more, based on 100 parts by weight of the negative electrode composition, the content of the pore ensuring material is 0.1 part by weight or more and 20 parts by weight or less, and the weight ratio of the linear conductive material to the pore ensuring material is 1:10 to 1:120.
[0048] The main feature of the negative electrode composition according to the present invention is that in a negative electrode using a silicon-based active material to maximize the capacity, a certain content of a pore ensuring material is used to simplify the pore structure, which is a problem of pure Si, and the resulting conductive network problem is solved by including a specific content of a linear conductive material.
[0049] Hereinafter, the negative electrode composition according to the present application will be described in detail.
[0050] In an exemplary embodiment of the present application, the silicon-based active material comprises one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, 90 parts by weight or more of SiOx (x = 0) may be included.
[0051] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be 90 parts by weight or more, preferably 92 parts by weight or more, and more preferably 93 parts by weight or more, and the content may be 100 parts by weight or less, preferably 99 parts by weight or less, and more preferably 95 parts by weight or less.
[0052] In an exemplary embodiment of the present application, the silicon-based active material may be SiOx (x = 0).
[0053] In an exemplary embodiment of the present application, for the silicon-based active material, in particular, pure silicon (Si) may be used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material may mean pure Si (SiOx (x = 0)) that is not combined with other particles or elements within the above range based on a total of 100 parts by weight of the silicon-based active material as described above.
[0054] That is, the silicon-based active material according to the present application uses pure Si and has the characteristic of being able to ensure a larger capacity of lithium than when SiOx (0<x<2) is used. Therefore, the fast charging capability and capacity characteristics may be excellent, but the negative electrode of pure Si may have problems such as ensuring pores, so the main feature of the silicon-based active material according to the present application is that it contains the above-mentioned pore ensuring material and the linear conductive material.
[0055] On the other hand, the average particle size (D50) of the silicon-based active material of the present invention can be 5μm to 10μm, specifically 5.5μm to 8μm, and more specifically 6μm to 7μm. When the average particle size is included in the above range, the specific surface area of the particles is included in a suitable range, thereby forming a viscosity of the negative electrode slurry within a suitable range. Therefore, the dispersion of the particles constituting the negative electrode slurry is promoted. In addition, the size of the silicon-based active material has a value equal to or greater than the lower limit value range, and the contact area between the silicon particles and the conductive material is excellent due to the composite composed of the conductive material and the binder in the negative electrode slurry, so the possibility of the conductive network continuing increases, thereby increasing the capacity retention rate. On the other hand, when the average particle size satisfies the above range, excessively large silicon particles are eliminated, forming a smooth negative electrode surface, and therefore, the phenomenon of uneven current density during charge and discharge can be prevented.
[0056] In an exemplary embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of the silicon-based active material is preferably 0.01 to 150.0 m 2 / g, more preferably 0.1 to 100.0 m 2 / g, particularly preferably 0.2 to 80.0 m 2 / g, most preferably 0.2 to 18.0 m 2 / g. The BET specific surface area is measured by DIN 66131 (using nitrogen).
[0057] In an exemplary embodiment of the present application, the silicon-based active material may be present, for example, in a crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure or be present in the form of a film or coating containing silicon.
[0058] In an exemplary embodiment of the present application, a negative electrode composition is provided, the negative electrode composition including the silicon-based active material in an amount of 60 parts by weight or more based on 100 parts by weight of the negative electrode composition.
[0059] In another exemplary embodiment of the present application, the content of the silicon-based active material may be 60 parts by weight or more and 95 parts by weight or less, based on 100 parts by weight of the negative electrode composition.
[0060] In yet another exemplary embodiment, the content of the silicon-based active material may be 60 parts by weight or more, preferably 60.5 parts by weight or more, more preferably 61 parts by weight or more, based on 100 parts by weight of the negative electrode composition, and the content may be 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 85 parts by weight or less.
[0061] The negative electrode composition according to the present application uses a silicon-based active material with a significantly high capacity within the above range. That is, when the silicon-based active material is used in an amount exceeding the above range, even if the combination of the linear conductive material and the pore ensuring material of the present invention is used, the service life characteristics cannot be ensured, but the battery performance evaluation result is poor, and when the amount of the silicon-based active material is less than the above range, although the service life characteristics can be ensured, the capacity characteristics and energy density are greatly reduced, so that when a negative electrode with the same capacity is manufactured, the thickness of the active material layer increases, and the fast charging performance is also poor.
[0062] The present application is characterized in that, by using a silicon-based active material within the above range, the volume expansion is controlled to such an extent that the capacity characteristics can be maximized at the same time, and the contents of a linear conductive material and a pore securing material to be described below are optimized.
[0063] In an exemplary embodiment of the present application, the silicon-based active material may have a non-spherical form, and the sphericity thereof is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, and for example, 0.85 to 0.9.
[0064] In the present application, the sphericity is determined by the following Formula 1, where A is an area, and P is a boundary line.
[0065] [Formula 1]
[0066] 4πA / P 2
[0067] In an exemplary embodiment of the present application, the negative electrode composition may include a pore ensuring material.
[0068] When using silicon-based active materials as described above, lithium insertion and extraction need to occur uniformly at the upper and lower ends of the electrode to ensure service life stability. However, as an existing conductive material, when a dot-shaped conductive material is used, the diffusion resistance of lithium ions is increased by blocking the pores in the electrode structure, and this resistance causes different degrees of degradation of the electrode at the upper and lower ends of the electrode during lithium insertion and extraction reactions.
[0069] In order to solve the above problems, the negative electrode composition according to the present application is characterized in that dot-shaped conductive materials are removed and a pore securing material is included in an amount of 0.1 parts by weight or more and 20 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0070] In an exemplary embodiment, the negative electrode composition according to the present application is characterized in that, based on 100 parts by weight of the negative electrode composition, the pore ensuring material is included in an amount of 0.1 parts by weight or more and 20 parts by weight or less, preferably 0.5 parts by weight or more and 19 parts by weight or less, and more preferably 0.7 parts by weight or more and 19 parts by weight or less.
[0071] That is, the negative electrode composition according to the present application has advantages in that pores between particles can be ensured, and a pore structure in which lithium ion diffusion can occur can be ensured by including the above-mentioned parts by weight of the pore ensuring material that does not react with lithium ions.
[0072] Furthermore, the pores ensure that the material may be metal oxide particles which are non-conductors.
[0073] In particular, when the above-mentioned pore ensuring material is used, even when a side reaction layer is partially formed in the active material, lithium ions can be uniformly dispersed in the electrode by ensuring the lithium ion path in the electrode, and since the pore ensuring material is included in the said content, the negative electrode composition according to the present application is characterized in that the service life stability of the electrode can be ensured by inducing a uniform reaction at the upper and lower ends of the electrode.
[0074] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the pore ensuring material is an inorganic oxide having a lower reactivity with lithium than the silicon-based active material. That is, the pore ensuring material may be an inorganic oxide having a lower reactivity with lithium or no reactivity than the silicon-based active material.
[0075] In an exemplary embodiment of the present application, the pores ensure that the material can exhibit an amorphous or crystalline form.
[0076] In an exemplary embodiment of the present application, the pore ensuring material is composed of an oxide of a non-transition metal, or an oxide having low reactivity with lithium ions, so that even if charging and discharging is performed between lithium ions and the silicon-based active material, any oxide can be used without restriction as long as it is an oxide whose composition or structure does not change due to the band structure between the electrode and the electrolyte.
[0077] In an exemplary embodiment of the present application, the pore securing material may be Al2O3; CaO; CeO2; MgO; or ZrO2, but is not limited thereto as long as it can be used to secure the pores in the above-mentioned negative electrode.
[0078] In the related art, only graphite compounds are generally used as negative electrode active materials, but recently, as the demand for high-capacity batteries increases, attempts to mix and use silicon-based active materials have increased in order to increase capacity. However, in the case of silicon-based active materials, even if the characteristics of the silicon-based active material itself are partially adjusted as described above, the volume expands rapidly during charge and discharge, so that in some cases, the problem of damage to the conductive path formed in the negative electrode active material layer may occur.
[0079] Furthermore, when the above-mentioned parts by weight of the pore ensuring material is used while removing the dot-shaped conductive material as described above, it may be difficult to ensure a conductive path because the pore ensuring material exhibits the characteristics of a non-conductor.
[0080] Therefore, the present application may include a linear conductive material in the negative electrode composition, thereby having a characteristic of being able to compensate for the pore securing material being a non-conductor and simultaneously reducing electrode resistance.
[0081] Generally, the existing silicon-based negative electrode may include a point-shaped conductive material and a surface-shaped conductive material.
[0082] In an exemplary embodiment of the present application, a negative electrode composition further including a negative electrode conductive material is provided, wherein the content of the negative electrode conductive material is 5 parts by weight or more and 15 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0083] In another exemplary embodiment, the negative electrode conductive material may be contained in an amount of 5 parts by weight or more and 15 parts by weight or less, preferably 13 parts by weight or less, and 5 parts by weight or more, specifically 7 parts by weight or more, based on 100 parts by weight of the negative electrode composition.
[0084] In this case, the negative electrode conductive material may include: a point-shaped conductive material; or a surface-shaped conductive material.
[0085] The dot-shaped conductive material can be used to improve the conductivity of the negative electrode, and means a conductive material in the form of balls or dots that has conductivity without inducing chemical changes. Specifically, the dot-shaped conductive material can be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and in terms of achieving high conductivity and excellent dispersibility, carbon black may be preferably included.
[0086] The planar conductive material can increase the surface contact between silicon particles in the negative electrode to improve conductivity while suppressing disconnection of the conductive path due to volume expansion, and can be expressed as a plate-shaped conductive material or a block-type conductive material. The planar conductive material can include at least one selected from the group consisting of plate-shaped graphite, graphene, graphene oxide, and graphite flakes, and can preferably be plate-shaped graphite.
[0087] First, when carbon black is used as a dot conductive material in a silicon-based negative electrode, the advantage is that it is inexpensive in terms of process, but in order to achieve the effect, a high proportion of carbon black needs to be included in the negative electrode composition. Since such a high proportion of dot conductive material needs to be used, gas generation at high temperatures has become a problem, and the stability of the negative electrode has deteriorated due to gas generation.
[0088] In addition, plate-like graphite used as a planar conductive material has a suitable price, has suitable rigidity, and acts as a buffer when rolling a silicon-based negative electrode due to its soft form, and also has a high specific surface area, so it has the characteristic of being able to form a conductive network between active materials. However, compared with the silicon-based active material used, the planar conductive material needs to be contained in an amount greater than a certain amount, so that despite having the above-mentioned properties, there is also a limitation in including a high content of silicon-based active materials in the negative electrode active material, which makes it impossible to maximize the capacity characteristics.
[0089] An exemplary embodiment of the present application is characterized in that, in particular, the linear conductive material includes SWCNTs; and MWCNTs.
[0090] In the present application, the specific surface area of the SWCNT may be 900 m 2 / g to 1500m 2 / g, and the average diameter may be 0.5 μm or more and 3 μm or less.
[0091] As described above, the SWCNT is long and has a high specific surface area, and thus has the most effective characteristics for forming a conductive network between silicon-based active materials. However, the SWCNT has the disadvantage of being very expensive, and when an excessive amount of SWCNT is used, a SWCNT dispersant used together is included, resulting in a decrease in rigidity.
[0092] In the present application, the specific surface area of the MWCNT may be 100 m 2 / g to 500m 2 / g, and the average diameter may be 10 μm or more and 20 μm or less.
[0093] In an exemplary embodiment of the present application, the MWCNT may satisfy a wall number of 5 to 20.
[0094] The MWCNT has a smaller specific surface area than the SWCNT and is inferior to the SWCNT in length, but is equivalent to a material having extremely excellent properties compared to the above-mentioned point-shaped and surface-shaped conductive materials.
[0095] In the present application, SWCNT has a high specific surface area and a large aspect ratio, while MWCNT is used in a relatively aggregated form (bundle form) and is therefore located on the surface of the silicon-based active material, which makes it difficult to achieve connection between the active materials. That is, SWCNT is used for long-distance connection, while MWCNT is used for mixing the particle surface with the binder complex.
[0096] In an exemplary embodiment of the present application, there is provided a negative electrode composition including the linear conductive material in an amount of 0.1 parts by weight or more and 5 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0097] In another exemplary embodiment, the content of the linear conductive material may be 0.1 parts by weight or more and 5 parts by weight or less, preferably 0.15 parts by weight or more and 4 parts by weight or less, and more preferably 0.15 parts by weight or more and 1.0 parts by weight or less, based on 100 parts by weight of the negative electrode composition.
[0098] In an exemplary embodiment of the present application, since the negative electrode composition contains a linear conductive material and satisfies the composition and ratio, the negative electrode composition is characterized in that the service life characteristics of the existing lithium secondary battery are not greatly affected, and the battery has more sites that can be charged and discharged, so the output characteristics at a high C rate are excellent.
[0099] In an exemplary embodiment of the present application, there is provided a negative electrode composition, wherein a total weight part of the pore ensuring material and the linear conductive material is 0.1 parts by weight or more and 30 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0100] In another exemplary embodiment, the total weight of the pore ensuring material and the linear conductive material may be 0.1 parts by weight or more and 30 parts by weight or less, preferably 0.5 parts by weight or more and 25 parts by weight or less, and more preferably 0.7 parts by weight or more and 20 parts by weight or less, based on 100 parts by weight of the negative electrode composition.
[0101] The above parts by weight means that an optimum ratio of pores and conductive paths can be ensured, and features that capacity characteristics in a pure Si negative electrode can be ensured and life characteristics and rapid charge characteristics can be ensured.
[0102] The negative electrode conductive material according to the present application has a completely different structure from the positive electrode conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application is used to capture the contact points between the silicon-based active materials in which the electrode volume expansion caused by charging and discharging is very large, and the positive electrode conductive material is used to play a buffering role during rolling while imparting partial conductivity, and its structure and function are completely different from those of the negative electrode conductive material of the present invention.
[0103] In addition, the negative electrode conductive material according to the present application is applied to the silicon-based active material, and has a completely different structure from the conductive material applied to the graphite-based active material. That is, the conductive material used for the electrode with the graphite-based active material has only small particles relative to the active material, and thus has the characteristics of improving the output characteristics and imparting partial conductivity, and its structure and function are completely different from the structure and function of the negative electrode conductive material applied together with the silicon-based active material in the present invention.
[0104] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the negative electrode binder includes one or more selected from the group consisting of a rubber-based binder; and a water-based binder.
[0105] In an exemplary embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials whose hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.
[0106] The negative electrode binder according to an exemplary embodiment of the present application plays the role of supporting the active material and the conductive material so as to prevent the negative electrode structure from being twisted and deformed during the volume expansion and relaxation of the silicon-based active material, and when the above-mentioned role is met, all general binders can be applied, specifically, water-based binders can be used, and more specifically, PAM-based binders can be used.
[0107] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the negative electrode binder includes an aqueous binder, and the content of the negative electrode binder is 5 parts by weight or more and 15 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0108] In another exemplary embodiment, the negative electrode binder may be contained in an amount of 5 parts by weight to 15 parts by weight, preferably 7 parts by weight to 13 parts by weight, and more preferably 9 parts by weight to 12 parts by weight, based on 100 parts by weight of the negative electrode composition.
[0109] In an exemplary embodiment of the present application, the content of the negative electrode binder may be 3 parts by weight or more and 10 parts by weight or less, based on 100 parts by weight of the silicon-based active material.
[0110] In another exemplary embodiment, the content of the negative electrode binder may be 3 parts by weight or more and 10 parts by weight or less, preferably 3.5 parts by weight or more and 10 parts by weight or less, and more preferably 5 parts by weight or more and 10 parts by weight or less, based on 100 parts by weight of the silicon-based active material.
[0111] In the case of the negative electrode for lithium secondary batteries according to the present application, in order to maximize the capacity characteristics, the silicon-based active material is used in the weight parts, and the volume expansion during charge and discharge is greater than when the existing carbon-based active material is used as the main active material. Therefore, the negative electrode for lithium secondary batteries according to the present application is characterized in that by including the negative electrode binder in the above content parts, the volume expansion caused by the charge and discharge of the high-rigidity silicon-based active material can be effectively suppressed.
[0112] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, the negative electrode comprising: a negative electrode collector layer; and a negative electrode active material layer formed on one surface or both surfaces of the negative electrode collector layer, the negative electrode active material layer comprising the negative electrode composition according to the present application.
[0113] Figure 1 1 is a diagram showing a stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, it can be confirmed that the negative electrode 100 for a lithium secondary battery includes a negative electrode active material layer 20 on one surface of a negative electrode collector layer 10, and Figure 1 It is shown that the negative electrode active material layer is formed on one surface, but the negative electrode active material layer may be included on both surfaces of the negative electrode collector layer.
[0114] In an exemplary embodiment of the present application, the negative electrode for a lithium secondary battery may be formed by applying a negative electrode slurry including the negative electrode composition to one surface or both surfaces of the negative electrode collector layer and drying the negative electrode slurry.
[0115] In this case, the negative electrode slurry may include: the negative electrode composition described above; and a slurry solvent.
[0116] In an exemplary embodiment of the present application, the solid content of the negative electrode slurry may satisfy 5% or more and 55% or less.
[0117] In another exemplary embodiment, the solid content of the negative electrode slurry may satisfy a range of 5% or more and 55% or less, preferably 7% or more and 35% or less, and more preferably 10% or more and 30% or less.
[0118] The solid content of the negative electrode slurry may mean the content of the negative electrode composition contained in the negative electrode slurry, and may mean the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.
[0119] When the solid content of the negative electrode slurry satisfies the above range, the present invention is characterized in that the viscosity is suitable during the formation of the negative electrode active material layer, so that the negative electrode active material layer can be effectively formed by minimizing the particle aggregation phenomenon of the negative electrode composition. In addition, the negative electrode composition according to the present application contains a high content of silicon-based active material by containing a linear conductive material, and is characterized in that fast charging performance and battery performance are excellent.
[0120] In an exemplary embodiment of the present application, the slurry solvent may be used without limitation as long as the slurry solvent can dissolve the negative electrode composition, and specifically, water, acetone, or NMP may be used.
[0121] In an exemplary embodiment of the present application, the negative electrode collector layer generally has a thickness of 1 μm to 100 μm. The negative electrode collector layer is not particularly limited as long as the negative electrode collector layer has high conductivity and does not cause chemical changes in the battery, for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode collector layer can also increase the bonding strength of the negative electrode active material by forming fine concave-convex on its surface, and the negative electrode collector layer can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0122] In an exemplary embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the thickness of the negative electrode collector layer is 1 μm or more and 100 μm or less, and the thickness of the negative electrode active material layer is 10 μm or more and 500 μm or less.
[0123] In the present application, the thickness of the negative electrode active material layer may refer to the thickness of a single layer of the negative electrode active material layer when formed on one surface of the negative electrode current collector layer.
[0124] However, the thickness may be variously modified according to the type and purpose of the negative electrode used, and is not limited thereto.
[0125] In an exemplary embodiment of the present application, the porosity of the negative electrode active material layer may satisfy a range of 30% or more and 60% or less.
[0126] In another exemplary embodiment, the porosity of the negative electrode active material layer may satisfy a range of 30% or more and 60% or less, preferably 35% or more and 55% or less, and more preferably 39% or more and 54% or less.
[0127] The porosity varies depending on the composition and content of the silicon-based active material, the conductive material and the binder contained in the negative electrode active material layer, and in particular, since the silicon-based active material, the pore ensuring material and the linear conductive material according to the present application are contained in specific compositions and content parts, the above-mentioned ranges are satisfied, thereby, being characterized in that the conductivity and resistance in the electrode have appropriate ranges.
[0128] In an exemplary embodiment of the present application, a lithium secondary battery is provided, the lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
[0129] Figure 2 1 is a diagram showing a stacking structure of a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, a negative electrode 100 for a lithium secondary battery can be confirmed, the negative electrode including a negative electrode active material layer 20 on one surface of a negative electrode collector layer 10, and a positive electrode 200 for a lithium secondary battery can be confirmed, the positive electrode including a positive electrode active material layer 40 on one surface of a positive electrode collector layer 50, and the negative electrode 100 for a lithium secondary battery and the positive electrode 200 for a lithium secondary battery are shown to be formed in a structure in which the electrodes are stacked with a separator 30 interposed therebetween.
[0130] A secondary battery according to an exemplary embodiment of the present specification may particularly include the above-mentioned negative electrode for a lithium secondary battery. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described in detail, its specific description will be omitted.
[0131] The positive electrode may include a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector and including the positive electrode active material.
[0132] In the positive electrode, the positive electrode collector is not particularly limited as long as the positive electrode collector has conductivity without causing chemical changes in the battery, for example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode collector can generally have a thickness of 3 to 500 μm, and the adhesion of the positive electrode active material can also be improved by forming fine concave and convex on the surface of the collector. For example, the positive electrode collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0133] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material includes: a layered compound such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) or a compound replaced by one or more transition metals; a lithium iron oxide such as LiFe3O4; a lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; Ni-site lithium nickel oxide, represented by the chemical formula LiNi 1-c2 M c2 O2 (herein, M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and c2 satisfies 0.01≤c2≤0.3); lithium manganese composite oxide, represented by the chemical formula LiMn 2-c3 M c3 O2 (herein, M is at least any one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and c3 satisfies 0.01≤c3≤0.1) or Li2Mn3MO8 (herein, M is at least any one selected from the group consisting of Fe, Co, Ni, Cu and Zn); LiMn2O4, wherein Li in the chemical formula is partially replaced by alkaline earth metal ions, etc., but is not limited thereto. The positive electrode may be Li metal.
[0134] The positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material.
[0135] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the battery to be constructed. Specific examples thereof include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof can be used.
[0136] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples thereof may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, and any one thereof or a mixture of two or more thereof may be used.
[0137] The diaphragm separates the negative electrode from the positive electrode, and provides a channel for lithium ion movement, and can be used without particular restriction, as long as the diaphragm is generally used as a diaphragm in a secondary battery, and in particular, preferably has excellent moisture retention for the electrolyte and has a diaphragm with low resistance to the movement of ions in the electrolyte. Specifically, a porous polymer film can be used, for example, a porous polymer film formed by a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer and an ethylene / methacrylate copolymer, or a laminated structure of more than two layers thereof. In addition, a typical porous non-woven fabric can also be used, for example, a non-woven fabric made of glass fiber, polyethylene terephthalate fiber, etc. with a high melting point. In addition, a coated diaphragm comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or multilayer structure.
[0138] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., which may be used to prepare lithium secondary batteries, but are not limited thereto.
[0139] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.
[0140] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used.
[0141] In particular, among carbonate-based organic solvents, ethylene carbonate and propylene carbonate as cyclic carbonates can be preferably used because the cyclic carbonates have a high dielectric constant as a high-viscosity organic solvent and thus dissociate lithium salts well, and when the cyclic carbonates are mixed with low-viscosity and low-dielectric-constant linear carbonates such as dimethyl carbonate and diethyl carbonate in an appropriate ratio, an electrolyte with high conductivity can be prepared, so such a combined use is more preferred.
[0142] As the metal salt, a lithium salt can be used. The lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte. For example, as the anion of the lithium salt, one or more selected from the group consisting of the following anions can be used: - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2- 、SCN - and (CF3CF2SO2)2N - .
[0143] In the electrolyte, in order to improve the service life characteristics of the battery, inhibit the reduction of the battery capacity and improve the discharge capacity of the battery, in addition to containing the above-mentioned electrolyte components, one or more additives may be further included, for example, halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride.
[0144] An exemplary embodiment of the present invention provides a battery module including the secondary battery as a unit cell and a battery pack including the battery module. The battery module and the battery pack include a secondary battery having high capacity, high rate performance and cycle performance, and thus can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.
[0145] [Mode of invention]
[0146] Hereinafter, preferred embodiments will be proposed to help understand the present invention, but these embodiments are provided only to illustrate the present invention, and it is clear to those skilled in the art that various changes and modifications can be made within the scope and technical concept of the present invention, and naturally, such changes and modifications also fall within the scope of the appended claims.
[0147] <Preparation Example>
[0148] <Preparation of negative electrode>
[0149] <Example 1>
[0150] A negative electrode slurry (solid concentration of 28 wt %) was prepared by adding Si (average particle size (D50): 5 μm) as a silicon-based active material, a pore ensuring material (Al2O3), a second conductive material, SWCNT as a linear conductive material, and polyacrylamide (PAM) as a binder in a weight ratio of 79:0.75:10:0.25:10 to distilled water as a solvent for forming a negative electrode slurry.
[0151] The SWCNTs satisfy a BET specific surface area of 1000 to 1500 m 2 / g, an aspect ratio of 10000 or more, and an average diameter of 1.0 μm or more. As the SWCNT, a dispersion of SWCNT in CMC was used. As the second conductive material, plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm).
[0152] As a specific mixing method, after dispersing the SWCNT, the second conductive material, the pore ensuring material, the binder and water at 2500 rpm for 30 minutes using a homomixer, the silicon-based active material is added thereto, and then the resulting mixture is dispersed at 2500 rpm for 30 minutes to prepare a negative electrode slurry.
[0153] Both surfaces of a copper current collector (thickness: 15 μm) as a negative electrode current collector layer were coated with the negative electrode slurry at 87.7 mg / 25 cm 2 The copper current collector was coated with a loading amount of , and the copper current collector was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 27 μm), which was used as a negative electrode (thickness of the negative electrode: 42 μm).
[0154] A negative electrode was prepared in the same manner as in Example 1, except that the parts by weight in Example 1 were changed to parts by weight in Table 1 below.
[0155]
[0156] In Table 1 above, the porosity of the negative electrode including the volume of the pore ensuring material was calculated as follows.
[0157]
[0158] <Comparative Example 5>
[0159] The Si (average particle size (D50): 5 μm) as a silicon-based active material, SWCNT as a linear conductive material, and carbon black C (specific surface area: 58 m 2 / g, diameter: 37nm), a second conductive material and polyacrylamide (PAM) as a binder were added to distilled water as a solvent for forming a negative electrode slurry in a weight ratio of 70:9.79:10:0.21:10 to prepare a negative electrode slurry (solid concentration: 28wt%).
[0160] The SWCNTs satisfy a BET specific surface area of 1000 to 1500 m 2 / g, an aspect ratio of 10000 or more, and an average diameter of 1.0 μm or more. As the SWCNT, a dispersion of SWCNT dispersed in CMC was used. As the second conductive material, plate-like graphite (specific surface area 17 m 2 / g, average particle size (D50) 3.5μm).
[0161] As a specific mixing method, after dispersing the SWCNT, carbon black C, the second conductive material, the binder, and water at 2500 rpm for 30 minutes using a homomixer, the silicon-based active material was added thereto, and then the resulting mixture was dispersed at 2500 rpm for 30 minutes to prepare a negative electrode slurry.
[0162] Both surfaces of a copper current collector (thickness: 26 μm) as a negative electrode current collector layer were coated with the negative electrode slurry at 87.7 mg / 25 cm 2 The copper current collector was coated with a loading amount of , and the copper current collector was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 33 μm), which was used as a negative electrode (thickness of the negative electrode: 41 μm).
[0163] <Comparative Example 6>
[0164] The silicon-based active material Si (average particle size (D50): 5 μm), carbon black C (specific surface area: 58 m 2 / g, diameter: 37nm), a pore ensuring material (Al2O3) and polyacrylamide (PAM) as a binder were added to distilled water as a solvent for forming a negative electrode slurry in a weight ratio of 70:10:10:10 to prepare a negative electrode slurry (solid concentration: 28wt%).
[0165] As a specific mixing method, after the carbon black C, the pore ensuring material, the binder, and water were dispersed at 2500 rpm for 30 minutes using a homomixer, the silicon-based active material was added thereto, and then the resulting mixture was dispersed at 2500 rpm for 30 minutes to prepare a negative electrode slurry.
[0166] Both surfaces of a copper current collector (thickness: 26 μm) as a negative electrode current collector layer were coated with the negative electrode slurry at 87.7 mg / 25 cm 2 The copper current collector was coated with a loading amount of , and the copper current collector was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 33 μm), which was used as a negative electrode (thickness of the negative electrode: 41 μm).
[0167] <Experimental example>
[0168] Experimental Example 1: Evaluation of the service life of a single battery
[0169] The secondary battery comprising the negative electrode manufactured in the embodiment and the comparative example was evaluated for service life using an electrochemical charger and discharger, and the capacity retention rate was evaluated. The secondary battery was subjected to in-situ cycle testing at 4.2-3.0V 1C / 0.5C, and the capacity retention rate was measured by charging and discharging the secondary battery at 0.33C / 0.33C (4.2-3.0V) every 50 cycles during the test, and the results are shown in Table 2.
[0170] Capacity retention rate (%) = {(discharge capacity at the Nth cycle) / (discharge capacity at the 1st cycle)}×100
[0171]
[0172] Experimental Example 2: Evaluation of tortuosity
[0173] After fabricating a symmetrical coin cell having the same electrodes as each other, the ionic resistance (R) was measured by electrochemical impedance spectroscopy (EIS) by measuring the interval showing a 45° slope in the low-frequency interval on the Nyquist plot. 离子 ). From these ionic resistances, the tortuosity is calculated using the following formula.
[0174]
[0175] In the formula, τ indicates the tortuosity, R 离子 indicates ionic resistance, ε indicates the porosity of the electrode, A indicates the area of the electrode, κ indicates the conductivity of the electrolyte, and t indicates the thickness of the electrode.
[0176]
[0177] Tortuosity evaluation is an index indicating how easy it is for ions to transfer through the hole path in the electrode, and the lower the value, the easier it is for the material involved in the actual electrochemical reaction to penetrate into the electrode. In this case, it can be confirmed that the electrode pores can be ensured by the hole ensuring material, and as the porosity increases, the number of paths through which the electrolyte can move increases, and the value of tortuosity improvement is shown (in the above table, the lower the tortuosity, the more the tortuosity is judged to be improved).
[0178] Experimental Example 3: Evaluation of initial cycle @SOC50 2.5C 0.1s discharge resistance (using a single cell to measure electrode resistance) Resistance
[0179] After measuring the capacity retention rate by charging and discharging the secondary battery at 0.33C / 0.33C (4.2~3.0V) every 50 cycles during the test in Experimental Example 1, the resistance value was measured within a certain period of time (0.1s) when discharged with a 2.5C pulse at SOC50, and the results are shown in Table 4 below.
[0180]
[0181] Experimental Example 4: Evaluation of Electrode Conductivity Measurement
[0182] The electrode resistance was measured by 4-point probe measurement, specifically, as Figure 3 As can be confirmed in the above, by passing a direct current between two outer probes of four probes spaced at the same interval to measure the voltage drop across the two inner probes, the resistance is calculated from the current and voltage values. Then, the electrode conductivity is calculated using the calculated resistance value and the distance between the probes, and the results are shown in the following Table 5.
[0183]
[0184] Experimental Example 5: PC Penetration Experiment
[0185] A certain amount (10 ml) of propylene carbonate (PC) was injected into the electrode surface punched into a certain area by a syringe, so that PC droplets were formed on the surface. Then, after covering the container to prevent the injected PC from evaporating, the time required for the solvent to completely penetrate into the electrode and the droplet to disappear was compared, and the corresponding results are shown in Table 6.
[0186]
[0187] As can be confirmed in Examples 1 to 8, the present application is characterized by adding a pore ensuring material capable of maintaining the porosity of the electrode while maximizing the diffusion of lithium ions. Therefore, since the point-shaped conductive material as the existing conductive material is removed and the pore ensuring material is used, the pore ensuring material is located between the particles in the electrode, so there is an advantage that pores capable of diffusion of lithium ions can be ensured.
[0188] In addition, the pore securing material is a non-conductor, and is characterized in that pores are secured by using a certain content, and a linear conductive material is additionally contained to compensate for the pore securing material and reduce electrode resistance. Therefore, the negative electrode composition according to the present application has the characteristics of being able to maintain pores even during lithium insertion and extraction in a pure Si electrode, and also securing conductivity and reducing electrode resistance.
[0189] That is, the main feature of the negative electrode composition according to the present invention is that, in the negative electrode using a silicon-based active material in order to maximize the capacity, a certain content of pore ensuring material is used so that the pore structure that is a problem of pure Si is simplified, and the conductive network problem caused by this is solved by including a specific content of linear conductive material.
[0190] Comparative Examples 1 and 2 correspond to the case where a hole ensuring material is included but the ratio of the linear conductive material to the hole ensuring material according to the present application is not satisfied, and Comparative Examples 3 and 4 correspond to the case where a hole ensuring material is included but the content exceeds the weight according to the present application. In addition, Comparative Example 5 corresponds to the case where no hole ensuring material is included. In addition, Comparative Example 6 corresponds to the case where a linear conductive material and a hole ensuring material are not used, but a dot conductive material and a hole ensuring material are used instead of a linear conductive material.
[0191] It can be confirmed that in this case, when compared with the embodiments, Comparative Examples 1 and 2 contain a small amount of pore-ensuring material that can ensure pores between particles and does not react with lithium ions, and therefore cannot achieve the above-mentioned effect, making it difficult to ensure the pore structure and resulting in poor evaluation results, while Comparative Examples 3 and 4, on the contrary, contain a large amount of pore-ensuring material that is a non-conductor, and it is difficult to ensure conductivity even if a linear conductive material is contained, thus resulting in poor evaluation results.
[0192] In the case of Comparative Example 5, it is difficult to ensure the desired pore structure because the pore ensuring material is not used. Comparative Example 6 is a case in which a dot-shaped conductive material is used instead of a linear conductive material. In this case, a side reaction layer of several tens of nanometers is formed in the dot-shaped conductive material, which blocks the pores instead. As a result, lithium ions cannot enter the lower end of the electrode, resulting in uneven lithium ion distribution at the upper and lower ends. Through these results, it can be confirmed that the silicon at the upper end is charged beyond the depth of charge, causing cracks in the active material and reducing the stability of the electrode life.
Claims
1. A negative electrode composition, the negative electrode composition comprising: a silicon-based active material; a pore ensuring material; a linear conductive material; and a negative electrode binder, wherein the silicon-based active material comprises one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) is 90 parts by weight or more, based on 100 parts by weight of the negative electrode composition, the content of the pore ensuring material is 0.1 part by weight or more and 20 parts by weight or less, and the weight ratio of the linear conductive material to the pore ensuring material is 1:2 to 1:
120.
2. The negative electrode composition according to claim 1, wherein based on 100 parts by weight of the negative electrode composition, the content of the silicon-based active material is 60 parts by weight or more.
3. The negative electrode composition according to claim 1, wherein based on 100 parts by weight of the negative electrode composition, the total weight parts of the pore ensuring material and the linear conductive material is 0.1 part by weight or more and 30 parts by weight or less.
4. The negative electrode composition according to claim 1, wherein based on 100 parts by weight of the negative electrode composition, the content of the linear conductive material is 0.1 part by weight or more and 5 parts by weight or less.
5. The negative electrode composition according to claim 1, wherein the linear conductive material is SWCNT; or MWCNT.
6. The negative electrode composition according to claim 5, wherein the MWCNT has 100 m 2 / g to 500m 2 / g specific surface area, and An average diameter of 10 μm or more and 20 μm or less.
7. The negative electrode composition according to claim 5, wherein the SWCNT has 900 m 2 / g to 1500m 2 / g specific surface area, and An average diameter of 0.5 μm or more and 3 μm or less.
8. The negative electrode composition according to claim 1, wherein the negative electrode binder comprises one or more selected from the group consisting of a rubber-based binder and an aqueous binder.
9. The negative electrode composition according to claim 1, the negative electrode composition further comprising a negative electrode conductive material, wherein based on 100 parts by weight of the negative electrode composition, the content of the negative electrode conductive material is 5 parts by weight or more and 15 parts by weight or less.
10. The negative electrode composition according to claim 1, wherein the pore ensuring material is an inorganic oxide having a lower reactivity with lithium than the silicon-based active material.
11. A negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery comprising: a negative electrode current collector layer; and a negative electrode active material layer formed on one surface or both surfaces of the negative electrode current collector layer, the negative electrode active material layer comprising the negative electrode composition according to any one of claims 1 to 10.
12. The negative electrode according to claim 11, wherein the negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, and the negative electrode active material layer has a thickness of 10 μm or more and 500 μm or less.
13. The negative electrode according to claim 11, wherein the negative electrode active material layer has a porosity of 30% or more and 60% or less.
14. A lithium secondary battery, the lithium secondary battery comprising: a positive electrode; the negative electrode for a lithium secondary battery according to claim 11; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
Citation Information
Patent Citations
Anode for lithium ion battery
JP2009080971A